Phenotypical Differences between Leishmania (Leishmania) amazonensis PH8 and LV79 Strains May Impact Survival in Mammal Host and in Phlebotomine Sand Flies - Tano, Fabia Tomie; Telleria, Erich Loza; Rêgo, Felipe Dutra; Coelho, Felipe Soares; de Rezende, Eloiza; Soares, Rodrigo Pedro; Traub-Cseko, Yara Maria; Stolf, Beatriz Simonsen (Pathogens (Basel, Switzerland), 2023)
We previously showed that L. (Leishmania) amazonensis promastigotes and amastigotes of the PH8 strain generated larger lesions in mice than LV79, and that lesion-derived amastigotes from the two strains differ in their proteomes. We recently reported that PH8 promastigotes are more phagocytized by macrophages. Promastigotes' membrane-enriched proteomes showed several differences, and samples of each strain clustered based on proteomes. In this paper, we show phenotypic differences between PH8 and LV79 promastigotes that may explain the higher virulence of PH8. We compared in vitro macrophage infections by day 4 (early) and day 6 (late stationary phase) cultures, resistance to complement, and LPG characteristics. PH8 promastigotes showed a higher infectivity and were more resistant to murine complement. LPG was different between the strains, which may influence the interaction with macrophages and survival to complement. We compared the infection of the permissive vector Lutzomyia longipalpis. PH8 was more abundant in the vector's gut 72 h after feeding, which is a moment where blood digestion is finished and the parasites are exposed to the gut environment. Our results indicate that PH8 promastigotes are more infective, more resistant to complement, and infect the permissive vector more efficiently. These data suggest that PH8 is probably better adapted to the sand fly and more prone to survive in the vertebrate host.
Keywords: infection; L. (L.) amazonensis; virulence; sand fly; LPG; complement